Upaya Peningkatan Pengetahuan dan Sikap Ibu Hamil dalam Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) melalui Pemberdayaan Kader - Ningsih, Lisma; Novira, Daisy (Politeknik Kesehatan Tanjung Karang, 2020)
As a breakthrough in accelerating the reduction in maternal mortality rates, the government since 2007 has launched a Maternity Planning and Prevention Complications Program (P4K). One effort to increase knowledge is health promotion with a community empowerment strategy. This study aimed to determine the effect of empowering cadres on the knowledge and attitudes of pregnant women about P4K. The study design used a quasi-experimental design by pre and post-test with control group design. The study population was all pregnant women, the sample was pregnant women who were selected purposively consisted of 60 people, 30 people in the intervention group, and 30 control groups. To analyze the data, the researcher used a paired t-test and independent t-test. The results showed that in the intervention group there was an increase of knowledge score (70,67) for before and (92,50) for after cadres empowerment, while in the control group there was no difference in the average knowledge score (74,67) before and (71,00) after an intervention (p-valueÂ 0,351). Moreover, In the intervention group, there was an increase in the attitude score of pregnant women before (78.67) and after (86.12) cadres empowerment, but in the control group there was no difference in the average attitude score before (77,46) and after (77,67) intervention (p-value=0,524). Empowering cadres can increase the knowledge and attitudes of pregnant women about P4K. It is hoped that the Health Office will further improve the implementation of P4K on an ongoing basis through the active role of the community, especially cadres.